COMPARATIVE INSIGHTS INTO HYDROGEN ABSTRACTION OF CCl3H BY SMALL OXYGEN-CONTAINING ANIONS MO− WITH M = Be, B, AND Al - junxi, liang; Yu, Duan; Jun, Bai; Qiong, Su; Zhenhua, Li; Lili, Zhang (Journal of the Chilean Chemical Society, 2021)
In the present work, the considered hydrogen abstraction (HAT) reactions of CCl3H molecule driven by three different small anions MO− (M = Be, B, and Al) have been investigated using electronic structure calculations. While full geometry optimizations were operated to locate all of the relevant stationary points using the DFT-BHandHLYP/aug-cc-pVTZ level, the potential-energy profiles were constructed using the coupled-cluster theory with extrapolation to complete basis set CCSD(T)/CBS. Our theoretical findings suggest that the most favored pathway determined for the HAT reactions mainly stems from the MO− type, namely, for facilitating the HAT pathway the B atom is predicted to be an inherent key in the BO−-reaction whereas it becomes O atom in both BeO−- and AlO−-reactions. Of the three favored pathways obtained here, the activations of the CCl3H in the presence of both BeO− and AlO− anions are significantly efficient, in which the energy barrier for the cleavage of the C-H bond with the assistance of BeO− was to be relatively low. Again, through the transition state theory the rate constants at 298-1000 K are also evaluated for the most favored HAT reactions studied here, indicating the lower the temperature, the faster the BO− chemical reaction.